2022
DOI: 10.1080/02813432.2022.2097616
|View full text |Cite
|
Sign up to set email alerts
|

The voice of the self: a typology of general practitioners’ emotional responses to situational and contextual stressors

Abstract: Objective To develop a comprehensive typology of emotional reactions associated with stress among general practitioners (GPs), grounded in their own experiences. Design Data was generated using observations and unstructured interviews, using Straussian grounded theory as the overarching methodology. The typology was built using multidimensional property supplementation. Setting Eleven health care centres in urban and rural communities in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The GP is subject to a multitude of demands from several sources: the voice of the situation , which captures explicit demands voiced in the situation; the voice of the system , which lends support to some actions and discourages others; the voice of the self , which accounts for the stress that results from threats to the GP’s personal needs [ 21 ]; and the voice of the profession , which captures a professional moral view that does not depend directly on the situation or context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GP is subject to a multitude of demands from several sources: the voice of the situation , which captures explicit demands voiced in the situation; the voice of the system , which lends support to some actions and discourages others; the voice of the self , which accounts for the stress that results from threats to the GP’s personal needs [ 21 ]; and the voice of the profession , which captures a professional moral view that does not depend directly on the situation or context.…”
Section: Discussionmentioning
confidence: 99%
“…By coding selectively around the highest-level concepts of the theory and simultaneously paying attention to the process, we eventually gained a deeper understanding of the circumstances that affect the moral actions of GPs. This led up to a second article in which we described the experience of stress—captured by the voice of the self —in general practice work, as well as the hypothesis that stress might guide the GP away from morally responsive action [ 21 ]. Although the voice of the profession is grounded in the same data as the previously mentioned concepts, we were able to elaborate on it only after coding selectively for it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the GPs role, our results suggest that developing a habit of offering private time and explaining professional secrecy would be beneficial. Considering the heavy workload that many GPs face [ 39 ], this might be perceived as an unrealistic task. One approach that might fit the bill, however, is a standardized split-visit model [ 1 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have often evaluated affective responses in relation to burnout. Recent studies have identified ‘trust, efficacy, understanding, and knowledge’ as four important personal needs that trigger negative emotional responses in physicians when they are threatened 29. Therefore, measuring medical professionals’ feelings of trust, recognition and respect may also help evaluate their emotional experiences.…”
Section: Introductionmentioning
confidence: 99%